The Effect of Educational Play Activities on the Social Development of Pre-School Children in Early Childhood - Ester; Lamria Situmeang (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Social development in pre-school children is crucial for their ability to interact and adapt to their environment. Educational play activities are believed to enhance this development through enjoyable and interactive learning experiences. Objective: To examine the effect of educational play activities on the social development of pre-school children. Methods: A quasi-experimental design with a pretest–posttest control group was conducted involving 30 pre-school children, divided equally into intervention and control groups. The intervention group participated in structured educational play activities for four weeks, three times per week. Social development was assessed using an observation sheet, and data were analyzed with Wilcoxon and Mann–Whitney tests. Results: The intervention group showed a significant improvement in social development after treatment (p = 0.002), while no significant change occurred in the control group (p = 0.134). Posttest comparison between groups revealed a significant difference (p = 0.005). Conclusion: Educational play activities are an effective strategy to enhance social development in pre-school children and can foster a fun, interactive, and developmentally appropriate learning environment.